Methods in Quaternary Ecology #5. Testate Amoebae (Protozoa) - Warner, Barry (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1988)
Summary Testate amoebae are unicellular animals with a discrete shell enclosing the cytoplasm The shells are readily preserved, are abundant in freshwater peatland and lake sediments, and can be identified to the species. Fossil testate amoebae were first discovered in the late 1800s in limnic sediments, but shortly there after were also found in peat deposits. Though testate amoebae are widely distributed throughout the northern hemisphere, they do not have cosmopolitan habitat preferences. Their most promising role in paleoecology lies indeciphering past hydrological conditions in peatlands. The future of testate amoebae analysis in Canada is bright, particularly inunderstanding fundamental processes of peatland development, and in peatland management schemes for forestry, and for the agricultural and horticultural industries.